ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI INDEKS HARGA SAHAM SEKTOR PROPERTI (Studi Pada Sektor Properti di Bursa Efek Indonesia) - Hedwigis Esti Riwayati; I Putu Jayantara (JWM (JURNAL WAWASAN MANAJEMEN), 2020)
Stock price index can be influenced by various factors both internal and external factors. This study aims to analyze the external factors that influence the stock price index including: the exchange rate of the rupiah, the SBI interest rate, and inflation. The population uses 56 property sector companies listed on the Indonesian Stock Exchange. The sampling technique uses saturated samples so that the entire population is sampled. The analytical tool in this study uses the Ordinary Least Square method which is processed by the E-views 9. The research results show that the strengthening of the rupiah exchange rate results in a decrease in the stock price index of the property sector listed on the Indonesia Stock Exchange. While changes in SBI interest rates and inflation did not affect fluctuations in the property sector stock price index. In this study shows that the exchange rate, SBI interest rates, and inflation are able to explain the stock price index of the property sector